Aktivitas Belajar Siswa pada Pembelajaran IPA dengan Model Discovery Learning di Kelas 9D SMP Negeri 01 Silo - Farah Ainurrohmah Izzati; Nadia Azdka Sri Wahyuni; Sofiah Sofiah; I Ketut Mahardika (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to examine student learning activities using the Discovery Learning learning model at SMP Negeri 01 Silo. The methods used to collect data are observation, interviews, and documents. From this study, data were obtained which were described as necessary. Based on the results of the analysis, it can be concluded that the Discovery Learning learning model can increase student learning activities in the classroom to be more active so that students pay more attention to the delivery of material, ask questions about material that has not been understood, and answer questions.